Lack of consideration of sex and gender in COVID-19 clinical studies - Emer Brady (Nature Portfolio, 2021)
Sex and gender have been associated with differences in SARS-CoV-2 incidence and clinical outcomes and therefore warrant consideration in study designs. Here, the authors assess registered and published clinical COVID-19 studies and find that sex-disaggregated analyses are infrequently presented or planned.